Untangling The Threads: Arbitration and Insolvency Processes Intersected - Chakraborty, Subhajit; Chandra, Siddhant; Ghosh , Souvik; Banerjee , Avik; Chaudhuri , Rajdip Bhadra; Bhowmik , Dipa (International Journal of Accounting and Economics Studies, 2025)
Increased global trade and the application of arbitration as the first-choice dispute resolution mechanism have caused more confluence between arbitration and insolvency. Arbitration deals with financial issues such as cross-border, debt recovery, and creditor-debtor conflict. Cases like Nortel, Lehman Brothers, and MF Global demonstrate the use of arbitration in addressing international insolvency conflicts. Nations such as Brazil, Chile, Peru, and Singapore have also enacted legislation favorable to arbitration in insolvency proceedings. This article suggests a framework for identifying which insolvency disputes may be arbitrable to clarify an international standard. Focusing specifically on India, the paper examines the overlap between arbitration and insolvency. In furtherance, this paper will attempt to analyze how arbitration and insolvency interact in Indian law. It seeks to clarify dispute resolution routes, which would make cross-border insolvency processes more cooperative and efficient.